The Development of Heat Substation for Drying Waste Heat Utilisation - Gariev, A. O.; Klemeš, Jiří Jaromír; Kusakov, S. K.; Tovazhnyanskyy, Leonid Leonidovich; Anokhin, P.; Kapustenko, P. O.; Arsenyeva, O. P.; Čuček, Lidija (The Italian Association of Chemical Engineering, 2014)
The problem solution of waste heat utilization at the tobacco factory is considered in this work. The analysis of the possibility of waste heat utilization and appropriate calculations of plate heat exchangers were carried out. The method for multi component mixture condensation calculation is used. This allows obtaining optimal parameters for the working conditions of the heat exchangers according to the energy efficiency retrofit of industrial enterprises. The design of heat substation for waste heat utilisation was developed.